Evaluation of pluripotency gene in Thai human dental pulp stem cells - Anantawat, Yada; Vongsavan, Kadkao; Sritanaudomchai, Hathaitip; Mitrakul, Kemthong; Arayapisit, Taweepong; Kraivaphan, Petcharat (Naresuan University Journal: Science and Technology (NUJST); Vol 24 No 2 (2016): May-August 2016, 2016)
The introduction of stem cells in regenerative medicine have given us valuable opportunities to repair the disfunctional tissues and organs of human.  The more variety of cell types stem cells can give rise to the more diseases and disability we can overcome.  ‘Pluripotency’ refers to the ability of stem cells to differentiate into all three germ layers.  The aim of this study was to evaluate the expression of pluripotency markers in Thai human dental pulp stem cells.  Stem cells was isolated and cultured from dental pulp tissue of 3 permanent teeth (DPSC 1-3) and 3 human exfoliated deciduous teeth (SHED1-3).  The total RNA was extracted from the dental pulp stem cells in passage 3-5.  The cDNA of DPSCs and SHEDs was measured the gene expression level of OCT-4, NANOG, SOX-2, and HNF-3b by RT-qPCR.  The statistical difference was determined by Mann-Whitney U test (P-value<0.05).  The result showed variation in level of pluripotency gene expression among both DPSC 1-3 and SHED 1-3.  Comparatively, the expression of OCT-4, NANOG, SOX-2 gene appeared to demonstrate higher trend in SHEDs.  Whereas, higher trend of HNF 3b gene expression was detected in DPSCs.  The genetic investigation of stem cell can reveal many useful data for the future of stem cell research and regenerative medicine.  This study was the first to provide comparative pluripotency markers information between SHED and DPSC of selected Thai patients. Keywords : Pluripotency markers, Dental pulp stem cells, Thai, Primary teeth, Permanent teeth
Keywords: Pluripotency markers, Dental pulp stem cells, Thai, Primary teeth, Permanent teeth